DIGITAL TECHNOLOGIES AND GENDERED REALITIES - Lingam, Lakshmi; Mkhwanazi, Nolwazi ([S.l.] : ROUTLEDGE INDIA, 2024)
The book explores the varying experiences and engagement of youth with smartphones and digital technologies in India and South Africa. It examines the process of meaning-making (identity construction) garnered through smartphone technology -- specifically relating to notions of love, sex, and sexuality. A keen reappraisal of the smartphone revolution, the essays underline the constant negotiations between technology and social institutions such as, family, schools, colleges\universities, religious groups, traditional community leaders, media, police, law, and governments. The volume looks at new forms of digital-based surveillance on girls, women and gender minorities and maps the responses of state, civil society and women's movements in tackling the divergent narratives of freedom versus control; empowerment versus violence. It specifically looks at how concepts of privacy', agency', autonomy' and consent' are being framed in the legal arena regarding young women, which may or may not be empowering of their agency and choices. Challenging notions about gender, technology and society, this book will be of great interest to scholars and researchers of sociology and social anthropology, politics, gender studies, and Global South studies.
Keywords: Smartphones; SOCIAL SCIENCE / Media Studies; SOCIAL SCIENCE / Gender Studies